2019
DOI: 10.3201/eid2503.170897
|View full text |Cite
|
Sign up to set email alerts
|

Acute Flaccid Myelitis Associated with Enterovirus D68 in Children, Argentina, 2016

Abstract: After a 2014 outbreak of severe respiratory illness caused by enterovirus D68 in the United States, sporadic cases of acute flaccid myelitis have been reported worldwide. We describe a cluster of acute flaccid myelitis cases in Argentina in 2016, adding data to the evidence of association between enterovirus D68 and this polio-like illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 13 publications
0
19
0
2
Order By: Relevance
“…Since the EV-D68 outbreak reported by the United States Centers for Disease Control and Prevention (CDC) in 2014, EV-D68 has been increasingly associated with acute flaccid myelitis in other researches [5][6][7][8][9][10][11][12][13]. Previous studies in 2014 showed that the odds of EV-D68 infection were 10.3 times higher for children with AFM than for respiratory pathogen panel (RPP)-tested controls [14].…”
Section: Discussionmentioning
confidence: 99%
“…Since the EV-D68 outbreak reported by the United States Centers for Disease Control and Prevention (CDC) in 2014, EV-D68 has been increasingly associated with acute flaccid myelitis in other researches [5][6][7][8][9][10][11][12][13]. Previous studies in 2014 showed that the odds of EV-D68 infection were 10.3 times higher for children with AFM than for respiratory pathogen panel (RPP)-tested controls [14].…”
Section: Discussionmentioning
confidence: 99%
“…Geographic involvement in the USA has varied each year. Cases have also been seen in other parts of the world, including Europe, Canada, Asia and South America 4 5 10 11. There is a slight male predominance in AFM cases1 8 with a recent, although small case series of 28 patients with AFM suggesting a predisposition in patients with a history of asthma, atopic dermatitis or head trauma 12.…”
Section: Epidemiology and Reporting Of Afmmentioning
confidence: 99%
“…13 Enterovirus-D68 circulation has likewise correlated with AFM outbreaks in Asia, 14 Europe, 15,16 and South America. 17 The epidemiological signal of AFM outbreak periods in the summer to fall of every other year since 2014 in the United States contrasts starkly with the background noise of sporadic cases during the intervening years (Fig 1). It is already evident in the Ayers et al 1 study and among US AFM cases overall from 2014 to 2018 that enterovirus-D68 has been the predominant pathogen detected.…”
mentioning
confidence: 94%